Improving Physical Fitness in Early Children through Cardio Circuit Games - Cahyo, Andi Nur; Purnama, Yudhi; Sahudi, Udi (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Early childhood is the beginning of a very good period of child growth in order to optimise child development, so knowledge about child development at an early age is very important for parents and teachers. This study aims to determine the effect of cardio circuit games on improving physical fitness in early childhood. This research was conducted using the one-group pretest-posttest experimental method. The sample in the content study was 40 elementary school students (6–9 years old) using a random sampling technique. Data were analysed using the normality prerequisite test and t-test to determine the effect of playing cardio circuits on the level of physical fitness. Cardio circuit games in the form of a combination of throwing, running, jumping, and squatting are packaged in the form of game movements across the track from post I to post VI. The results showed that the average pretest and posttest scores increased from 16.1 to 17.8, and the Sig. (2-tailed) is 0.000 greater than 0.05, so it can be concluded that there is an influence between playing cardio circuits and physical fitness levels. The average results of the pretest and posttest scores prove that there is a level of physical fitness for early childhood (lower elementary school students) through cardio circuit games.